Typical Murders Committed by Convicts in Prisons (Law and Safety, 2019)
One of the main elements of the forensic characteristics of murders committed by convicts in prisons is the modus operandi.It has been noted that the modus operandi and tools used in the commission of a crime are very important elements of the forensic characteristics of crimes. This is due to the fact that they are the main trace elements of the forensic characteristics of any crime and act as a “key” for the investigation of criminal offenses.Various views on the concept of “modus operandi” that exist in the forensic literature have been studied.It has been emphasized that the modus operandi of murders has the uniform structure that is inherent in all types of crimes, different from each other by the object of the attack.The author has supported the position of scholars in the forensic field, who offer to distinguish certain stages in the modus operandi (mechanism of criminal action); in particular, the following three stages have been distinguished in relation to murders committed by convicts in prisons: the preparatory stage, the stage of the murder, the stage of concealing the crime. At the same time the author understands the method of murder as the system of certain actions, methods, techniques used by the killer to achieve a criminal purpose. Thus, the method of murder involves three components: the method of preparation, the method of commission, and the method of concealing the crime.It has been emphasized that it is impossible to determine an exhaustive list of methods of preparing, committing and concealing murders by convicts in prisons, since each of the methods is individual and has its own specific features. The specificity of the methods is due to the specificity of the crime’s subject (convicted), the circumstances of the offense, the victim, the limited choice of tools. The choice of the method also depends on the criminal record of the offender.
Keywords: modus operandi; offender’s personality; murder; places of imprisonment